TaPUB57 confers drought tolerance, governs grain size and salt sensitivity by ubiquitinating TaEXPB3 in rice - Chunmei Yu; Min Wang; Long Li; Yuying Li; Yanfei Zhang; Jie Zhang; Xin Chen; Lili Yang; Chaonan Li; Jingyi Wang; Guangchao Liu; Matthew P Reynolds; et al. (Plant Stress)
Wheat (Triticum aestivum L.) is the widest cultivated crop in the world. Abiotic stress, such as drought and high salinity, dramatically impacts the growth and development of wheat and leads to remarkable yield loss. Understanding the underlying mechanisms of abiotic stress tolerance is of great importance to develop high yield varieties with wide adaptability. Ubiquitination is a major type of post-translational modification in eukaryotes. The plant U-Box (PUB) protein is the smallest family in the E3 ligase superfamily, and involved in the responses to various environmental stimuli. Currently, TaPUB57 has been cloned from wheat. It was induced by multiple abiotic stresses and phytohormone. Its ectopic expression increased grain size and drought tolerance, but caused hypersensitive to salt stress in rice. TaPUB57 interacted with and ubiquitinated TaEXPB3. Constitutive expression of TaEXPB3 resulted in small grain size and remarkably enhanced salt tolerance. Moreover, TaPUB57/TaEXPB3 co-expressing rice plants exhibited phenotypes of salt sensitivity and larger grain size relative to TaEXPB3 transgenic lines. Therefore, it is speculated that TaPUB57 acts on grain size and the salt tolerance by ubiquitinating TaEXPB3.